HYPOGLYCEMIC ACTIVITY OF ETHYL ACETATE FRACTION COMBINATION OF MORINDA FRUIT AND CINNAMON BARK USING GLUCOSE-INDUCED IN MICE - MUSFIROH, IDA; YUSUF, NURFADILAH; MOEKTIWARDOYO, MOELYONO (International Journal of Applied Pharmaceutics, 2021)
Objective: Noni fruit (Morinda citrifolia L) and cinnamon bark (Cinnamomum burmannii) are plants that have the hypoglycemic effect on their ethyl acetate fraction in the single dose. This study was to determine the hypoglycemic activity of the combination of ethyl acetate fraction (FEM) and cinnamon bark (FEC) in glucose-induced mice, as well as the dose of the combination of FEM and FEC which could have a hypoglycemic effect. Methods: The methods were including extraction using liquid-liquid extraction, identification by TLC, and assay of hypoglycemic activity in mice induced by oral glucose for a moment in the eight groups that were normal control, negative control, positive control, dose 1-5. The activity tests were performed at 30th, 60th, 90th and 120th of minutes. Results: The research showed that the yield of FEM and FEC were 5.25% and 8.05%. Identification of compounds by TLC showed that the FEM and FEC were 4 and 3 spots. The results of a hypoglycemic test showed that the combination of FEM and FEC on glucose-induced mice showed a decreased effect of mice blood glucose levels better than a single dose of these fractions. Conclusion: The hypoglycemic activity test at a combined dose of FEM 175 mg/kg BW and FEC 150 mg/Kg BW have provided hypoglycemic activity better compared to other dose groups with a percentage decrease in average relative blood glucose at the 30th, 60th, 90th, 120th minute were 29.57%, 44.94%, 43.40% and 40.55%, respectively. Thus, the combination of the FEM and FEC in glucose-induced mice gave a hypoglycemic effect in mice.